TINGKAT KEPATUHAN PASIEN GAGAL GINJAL KRONIK DALAM MENJALANI HEMODIALISA - Ni Putu Wiyani; I Made Sukarja; Wina Ni Made Krisnayani; Putu Intan Daryaswanti (Jurnal Kesehatan Medika Udayana, 2018)
Background: Chronic Kidney Failure is one of the important health problems in Indonesia and the world community. In Indonesia, according to data from Penetri (Persatuan Nefrologi Indonesia) the number of patients with kidney failure is estimated at 4500 people, but those detected suffering from terminal stage chronic kidney failure from those undergoing dialysis (hemodialysis) are only around 4 thousand - 5 thousand people. Cases of kidney failure in Indonesia are still relatively high every year, because there are still many Indonesian people not maintaining their diet and health. This means that chronic kidney failure ranks as one of the highest rates of disease causing death. The purpose of this study was to describe the level of adherence to patients with chronic kidney failure in undergoing a hemodialysis program in the hemodialysis room at Sanjiwani Hospital in Gianyar. Methods: This research is a descriptive observational type. This study uses a sampling technique that is purposive sampling with a total sample of 30 people. Results: In this study the results of the rate of compliance of CRF patients with hemodialysis were 27 respondents (90%) who were obedient and non-adherent as many as 3 respondents (10%). Thus most patients with chronic renal failure adhere to undergoing hemodialysis in the hemodialysis room of Sanjiwani Hospital in Gianyar. Conclusions: The conclusion of this study is that patients with chronic renal failure are expected to seek treatment regularly in accordance with the rules set by health workers. Delay of dialysis causes pulmonary complications, seizures, decreased consciousness, severe electrolyte disturbances, heart failure, which can cause death.Keywords : Chronic Kidney Failure; Hemodialysis, Compliance